Chemical aminoacylation of tRNAs with fluorinated amino acids for in vitro protein mutagenesis - Ye, Shijie; Ann Berger, Allison; Petzold, Dominique; Reimann, Oliver; Matt, Benjamin; Koksch, Beate (Beilstein Journal of Organic Chemistry, 2010)
This article describes the chemical aminoacylation of the yeast phenylalanine suppressor tRNA with a series of amino acids bearing fluorinated side chains via the hybrid dinucleotide pdCpA and ligation to the corresponding truncated tRNA species. Aminoacyl-tRNAs can be used to synthesize biologically relevant proteins which contain fluorinated amino acids at specific sites by means of a cell-free translation system. Such engineered proteins are expected to contribute to our understanding of discrete fluorines’ interaction with canonical amino acids in a native protein environment and to enable the design of fluorinated proteins with arbitrary desired properties.
Keywords: chemical aminoacylation; DfeGly; fluorinated amino acids; site-specific protein mutagenesis; TfeGly; TfmAla